Supressão e frequência da irrigação na cultura de abobrinha - Garcia, Amparo Cisneros (2015)
The zucchini (Cucurbita pepo L.) is a vegetable from the family Cucurbitaceae plant grown in Brazil in the North, Northeast and much of the Southeast and Midwest. It lies between the ten vegetables with higher economic value, with high importance, especially in Central and Southern of Brazil. In order to evaluate the influence of different times of withholding irrigation and irrigation frequency in the culture of zucchini, there were two experiments in the experimental area of Meteorological Station of the Federal University of Ceará, Fortaleza, Brazil. The experimental design was a randomized block consisting of five treatments and four replications for irrigation suppression experiment and six treatments and four replications for irrigation frequency of experiment. The treatments corresponding to the first experiment were withholding irrigation at 55 days (S55) after planting (DAP); S62 DAP; S69 DAP; S76 DAP and S83 DAP (unsuppressed). In the second experiment the treatments consisted of different frequencies of irrigation: Fi1 - daily; Fi2 - every two days; Fi3 - every three days; Fi4 - every four days; Fi5 - every five days and Fi6 - every six days, all irrigated with 100% ETo, calculated for weather station. It was evaluated the soluble solids proportion (SS), fruit diameter (DF), pulp thickness (EP), the number of fruits (NF), length (FL), average fruit weight (MF), and productivity (PROD) of the zucchini. It was also evaluated the net revenue for each treatment in both experiments. The treatments with withholding irrigation significantly influenced the average fruit weight, fruit length and productivity, with the highest values observed for the treatment without withholding irrigation, with the higher productivity of 25,142 kg ha-1. This treatment was also responsible for the highest economic return that was R$ 4,944.35 for hectare. The different irrigation frequencies significantly influenced the average fruit weight and productivity, both have greater value when irrigated daily, with the highest productivity 24,588 kg ha-1 . The daily irrigation also provided the highest value of R$ 4,683.77 for hectare net revenue.